2010
DOI: 10.1111/j.1751-7893.2010.00196.x
|View full text |Cite
|
Sign up to set email alerts
|

Mental health literacy among young people in a small US town: recognition of disorders and hypothetical helping responses

Abstract: There appears to be substantial room for improvement in mental health literacy among young people, and the development of interventions to enhance mental health literacy among students may be justified.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
81
0
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 75 publications
(88 citation statements)
references
References 16 publications
3
81
0
1
Order By: Relevance
“…The female students were more likely than were the male students to volunteer support to people with mental disorders, as observed in past studies (Holzinger et al, 2012). In addition, as in previous studies (Olsson and Kennedy, 2010), greater mental health literacy was linked to a higher willingness to provide help to people with mental disorders.…”
Section: Serra Et Alsupporting
confidence: 65%
“…The female students were more likely than were the male students to volunteer support to people with mental disorders, as observed in past studies (Holzinger et al, 2012). In addition, as in previous studies (Olsson and Kennedy, 2010), greater mental health literacy was linked to a higher willingness to provide help to people with mental disorders.…”
Section: Serra Et Alsupporting
confidence: 65%
“…Mental health literacy has been identified as an important, modifiable determinant in help seeking (Jorm, 2012); two recent studies indicated that young people who were able to identify symptoms as being a mental disorder were more likely to recommend telling an adult and less likely to recommend dealing with the problem alone (Wright et al, 2007;Olsson and Kennedy, 2010). However, only 42 percent of adolescent student respondents were able to correctly identify depression as a mental health problem or illness (Olsson and Kennedy, 2010).…”
Section: Introductionmentioning
confidence: 96%
“…4557, 2004). In addition to other suicide prevention strategies such as screening at risk individuals, reduction of lethal means, and psychiatric treatment, education and awareness programs are areas needing particular attention (Mann et al, 2005;National Research Council (US) and Institute of Medicine Committee on the Prevention of Mental Disorders and Substance Abuse Among Children, Youth, and Young Adults: Research Advances and Promising Interventions, (2009); Olsson and Kennedy, 2010;Michelmore and Hindley, 2012;Reavley and Jorm, 2012). In a survey of suicide prevention programs, Garland et al, 1989 reported that 95% of programs adhered to a theory that "youth suicide is most commonly a response to extreme stress or pressure and could happen to anyone."…”
Section: Introductionmentioning
confidence: 99%
“…Health literacy for mental health problems-aka mental health literacy [17]-has been shown to be limited in general population adults [18][19][20][21][22] and youth [23][24][25][26][27][28][29][30][31][32][33], whereby many people fail to recognize and correctly label common psychiatric disorders and are limited in their knowledge about how to take appropriate action for themselves and others. These findings have particular relevance for caregivers of children with mental health problems.…”
Section: Introductionmentioning
confidence: 99%